(untitled) (Research, Society and Development, 2024)
The use of solar energy has been increasing its space in the energy matrix. Brazil has great potential for applications using photovoltaic energy. This potential is not fully explored. Due to this, this research aims to evaluate the environmental impacts caused by the production, implementation, operation and maintenance of a 1 MW photovoltaic plant implemented in the Academic Unit located in Cabo de Santo Agostinho, Pernambuco, Brasil, one of the branches of the of the Federal Rural University of Pernambuco. The Control List Method ("checklist") was used to identify and qualitatively evaluate the most relevant impacts. The environmental assessment of the plant identified that the biggest impact in the planning phase was the attraction of people, due to the publicity of the project. In the implementation phase, deforestation and soil movement stood out, while visual pollution and the increase in the supply of electricity were the main impacts in the operation phase.